2017
DOI: 10.1038/srep45681
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Circulating Plasma Cells in Multiple Myeloma Using CD138 Antibody-Based Capture in a Microfluidic Device

Abstract: The necessity for bone marrow aspiration and the lack of highly sensitive assays to detect residual disease present challenges for effective management of multiple myeloma (MM), a plasma cell cancer. We show that a microfluidic cell capture based on CD138 antigen, which is highly expressed on plasma cells, permits quantitation of rare circulating plasma cells (CPCs) in blood and subsequent fluorescence-based assays. The microfluidic device is based on a herringbone channel design, and exhibits an estimated cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 33 publications
(54 reference statements)
1
42
0
Order By: Relevance
“…Finally, when antibody-based isolation of CTCs is used, depending on the choice of chemistry, the capture surfaces are often subject to high levels of cross-reactivity with off-target cells (e.g., erythrocytes and leukocytes) 39 . For example, in our previous study 40 , we observed a background of erythrocytes and leukocytes when avidin-biotin chemistry was used to immobilize antibodies in the microfluidic device, where avidin's strong positive charge 41 most likely caused ionic interactions with these cells. Likewise, using avidin-biotin chemistry, an HB-Chip 12 reported 14% purity of captured spiked in PC3 cells among captured WBCs in the channels, while in our device the capture purity of PC3 cells spiked into blood was twice as high as that result (28.0% ± 3.6%).…”
Section: Isolation Of Prostate Ctcs From Whole-blood Samples Of Cancementioning
confidence: 97%
See 1 more Smart Citation
“…Finally, when antibody-based isolation of CTCs is used, depending on the choice of chemistry, the capture surfaces are often subject to high levels of cross-reactivity with off-target cells (e.g., erythrocytes and leukocytes) 39 . For example, in our previous study 40 , we observed a background of erythrocytes and leukocytes when avidin-biotin chemistry was used to immobilize antibodies in the microfluidic device, where avidin's strong positive charge 41 most likely caused ionic interactions with these cells. Likewise, using avidin-biotin chemistry, an HB-Chip 12 reported 14% purity of captured spiked in PC3 cells among captured WBCs in the channels, while in our device the capture purity of PC3 cells spiked into blood was twice as high as that result (28.0% ± 3.6%).…”
Section: Isolation Of Prostate Ctcs From Whole-blood Samples Of Cancementioning
confidence: 97%
“…The design of the PDMS chip was adapted from our previously developed device 40 . The chip fabrication was carried out on a silicon wafer with two layers of highviscosity negative photoresist SU-8 (MicroChem Corp., USA) using a standard soft photolithography protocol: one for the microfluidic channels and the other for the HB elements.…”
Section: Chip Design and Fabricationmentioning
confidence: 99%
“…In 2007, Nagrath and coworkers used a microfluidic chip modified with an epithelial‐specific adhesion molecule (EpCAM) antibody to successfully separate untreated peripheral blood CTCs for the first time . At present, the microfluidic chip based on an antibody as the trapping probe has successfully detected CTCs . At the same time, as an artificial small molecule that is easier to preserve and modify than antibodies, the aptamer is more suitable for functional modification of microfluidic chips.…”
Section: Detection Of Circulating Tumor Cells By Electrochemical Biosmentioning
confidence: 99%
“…79 At present, the microfluidic chip based on an antibody as the trapping probe has successfully detected CTCs. [80][81][82][83] At the same time, as an artificial small molecule that is easier to preserve and modify than antibodies, the aptamer is more suitable for functional modification of microfluidic chips. For example, the microfluidic chip modified by nucleic acid aptamer sgc8 has successfully achieved the separation and capture of target cells from many samples with a capture efficiency of 80% and a specificity greater than 97%.…”
Section: Detection Of Circulating Tumor Cells By Electrochemical Biosmentioning
confidence: 99%
“…From the cytogenetic point of view, MM may be divided into two groups: hyperdiploid and non-hyperdiploid. Hyperdiploid genome is mostly characterized by trisomies of odd chromosomes (3,5,7,9,11,15,19,21) and is connected to better prognosis [5], while non-hyperdiploid genome is characterized by monosomies of chromosomes 8,13,14,16,17 and 22 and recurrent chromosomal translocations involving the immunoglobulin heavy chain (IgH) locus at 14q32. In MM, the most frequent chromosomal translocations are t(11;14)(q13;q32) (15-20% of MM patients) and t(4;14)(p16;q32) (12-15% of MM patients).…”
Section: Introductionmentioning
confidence: 99%